Adaptive Droop Control of the MTDC System With High-Capacity Energy Storage Based on Dynamic and Static Power Decoupling Method - Xie, Luyao; Guo, Xin; Wei, Chun; Zhang, Youbing; Chen, Yi; Liang, Congbin; Xue, Yuantian; Zhao, Ermin (Frontiers in Energy Research, 2021)
In a multiterminal DC (MTDC) system with a large number of different types of energy storage devices, the AC terminals and the energy storage devices need to cooperate to maintain the stability of the DC bus voltage. Due to the difference in the dynamic and static power capability of each energy storage unit, the dynamic and static power should be distributed separately. To solve the above problems, an adaptive droop control strategy based on the dynamic and static power decoupling is proposed in this paper. The impact of the virtual impedance values on the dynamic and static power flows between the DC voltage regulating terminals operating with the RC droop method is analyzed. Through optimized virtual capacitance and adaptive virtual resistance, the dynamic power and static power can be distributed according to the PCS capacity and the available charge–discharge battery capacity, respectively. In addition, a simple secondary control method is adopted to compensate the static deviation of the DC bus voltage. Finally, a six-terminal MTDC system model is established in Matlab/Simulink, and the simulation results verify the feasibility and effectiveness of the proposed control strategy.